PENGEMBANGAN PARIWISATA BERKELANJUTAN MELALUI APLIKASI SIMANIS TERINTEGRASI VIRTUAL TOUR DI DESA PADAK GUAR, LOMBOK TIMUR - Majid, Abdul Majid Junaidi; Hamidy, Rasyid Ridho; Karomi , Karomi (Universitas Mataram, 2025)
Tourism plays an important role as a strategic sector in driving economic growth and improving the welfare of local communities. Padak Guar Village in East Lombok Regency has great potential for marine tourism, especially in terms of its natural beauty and coastal culture. However, this potential has not been optimally managed due to limited promotional media and the low level of digital literacy among the community in marketing tourism destinations. This condition requires technological innovation to support the promotion and development of sustainable tourism in the village. This community service program aims to enhance the capacity of tourism managers and local MSMEs through the implementation of the SIMANIS Application integrated with a Virtual Tour. The program focuses on optimizing technology-based destination promotion. The activities were carried out through several stages, including needs analysis to identify main problems and tourism potential, followed by system design, application training, and digital content creation assistance. Evaluation was conducted to measure the program’s effectiveness and success. The results show a significant improvement in the community’s understanding of digital technology, reaching 85% of all participants. The number of tourism promotional contents uploaded via digital media increased by 275%, indicating active community participation in promoting destinations. Tourist visits also rose from 750 to 1,250 people per month, positively impacting the local economy. In addition, the average income of MSME actors around the tourist area increased by 30%. Overall, this activity successfully strengthened the community’s digital capacity and expanded the promotional reach of Padak Guar tourism. The implementation of the SIMANIS Application and the Virtual Tour website proved effective in improving destination promotion, expanding market reach, and supporting the realization of sustainable tourism in Padak Guar Village.